Developing positive behavioral skills among adolescents participating in basketball sports schools - Pocius, Eimantas; Malinauskas, Romualdas (Frontiers in Psychology, 2025)
IntroductionThe aim of this study is to evaluate the impact of a positive behavior skills development program on adolescents who participate in basketball sports schools.MethodsSixty-two adolescent athletes (Mage 15.83 ± 0.37) took part in this educational experiment. Participants were randomly selected from 2 basketball sports schools chosen from a list of basketball sports schools and divided into experimental (n = 30) and control (n = 32) groups. The experimental group participants were subjected to the effect of the positive behavior skills development program, which aimed to develop positive behavior skills among adolescents participating in basketball sports schools, including taking responsibility, positive self-evaluation, prosocial behavior with teammates, prosocial behavior with opponents, taking social responsibility, cooperation, assertiveness, empathy, self-control, ability to evaluate and convey emotions, ability to utilize one’s positive emotional experience, ability to comprehend and analyze emotions, and ability to control emotions. Positive behavior skills development activities were conducted by one of the researchers together with the sports school coaches. At the beginning and end of the educational experiment, participants from both the experimental and control groups completed the following questionnaires: Personal and Social Responsibility Questionnaire, Rosenberg Self-Esteem Scale, The Prosocial and Antisocial Behavior in Sport Scale, Social Skills Rating System-Secondary Student form, and Schutte Self-Report Inventory.ResultsThe positive behavior skills development activities implemented during the educational experiment had a positive and statistically significant impact on the positive behavior skills of the experimental group adolescents.DiscussionThe findings of the present study could be useful for educational programs developers who may consider integrating elements of this educational program into wider education systems.